Consumption of Private Goods as Substitutes for Environmental Goods in an Economic Growth Model - Antoci, A.; Galeotti, M.; Russu, P. (Nonlinear Analysis: Modelling and Control, 2005)
We analyze growth dynamics in an economy where a private good can be consumed as a substitute for a free access environmental good. In this context we show that environmental deterioration may be an engine of economic growth. To protect themselves against environmental deterioration, economic agents are forced to increase their labour supply to increase the production and consumption of the private good. This, in turn, further depletes the environmental good, leading economic agents to further increase their labour supply and private consumption and so on. This substitution process may give rise to self-enforcing growth dynamics characterized by a lack of correlation between capital accumulation and private consumption levels, on one side, and economic agents’ welfare, on the other. Furthermore, we show that agents’ self-protection consumption choices can generate indeterminacy; that is, they can give rise to the existence of a continuum of (Nash) equilibrium orbits leading to the same attracting fixed point or periodic orbit.